(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: Pituitary adenoma (PA) is a neoplasm that develops from anterior pituitary cells and accounts for 20-25% of all intracranial extracerebral tumors. In a functioning PA, a specific clinical syndrome develops, and, therefore, the diagnosis can be made early, when the tumor is small. In a non-functioning PA, the early stage is often asymptomatic and the disease is usually diagnosed only with the onset of visual impairment, with 3.5% to 16% of patients having blindness as an outcome. Purpose: To investigate changes in the visual field in pituitary adenomas with suprasellar extension and various anatomical positions of the optic chiasm. Materials and Methods: Ninety-six (100%) patients with a non-invasive PA with suprasellar extension were under surveillance at the Romodanov Neurosurgery Institute between 2015 and 2016, and underwent clinical neurological and ophthalmological examination and comprehensive neuroimaging evaluation. Inclusion criteria were a history of surgical procedure for a non-invasive PA with suprasellar extension, and visual impairment. Results and Discussion: Of the 96 patients, 50 (52%) had visual impairment, and were included in the analysis. Bitemporal visual field changes and homonymous hemianopia were found in 48 (96%) patients and 2 (4%) patients, respectively. Symmetric, asymmetric or markedly asymmetric chiasmal syndrome was found in 32 (67%), 11 (23%), and 5 (10%) patients, respectively. Of the 50 patients, 8 (16%) had a prefixed chiasm, and 3 (6%; patients with a bitemporal constriction of the visual fields) had a postfixed chiasm. Patients with pituitary adenoma may have a delayed onset of or no visual impairment due to the presence of a prefixed or postfixed chiasm. Conclusion: Static automated perimetry (SAP) is a sensitive and objective technique for detecting visual field defects in patients with PA with suprasellar extension. The SAP demonstrated characteristic visual field changes in temporal halves, with a degree of visual field loss ranging from mean deviation −1.26 to −19.31 dB.